Cultural Preservation through the Marching Tong of SMP Negeri 7 Bondowoso in Bondowoso Regency - Manuel Pratama, Ritchie; Utomo, Udi; Syah Sinaga, Syahrul (Universitas Negeri Semarang, 2024)
This research aims to explore the role of Marching Tong art at SMP Negeri 7 Bondowoso as a means of preserving local culture amidst the challenges of modernization and globalization. Using a case study approach and descriptive qualitative methods, this research collected data through participant observation, in-depth interviews with teachers, students and community leaders, as well as analysis of related documentation. The research results show that the Marching Tong not only functions as entertainment, but also as an effective educational medium in introducing cultural values to the younger generation. Through extracurricular activities and performances at various events, students are invited to understand and appreciate the meaning and values contained in this art, thereby contributing to the preservation of local culture. With collaboration between schools, local government and the local arts community, it is hoped that Marching Tong can continue to develop and become an integral part of Bondowoso's cultural identity. It is hoped that this research will provide new insight into the importance of preserving culture through traditional arts and encourage other schools to develop similar programs in an effort to maintain cultural diversity in Indonesia.